Pembuatan Aplikasi Penerimaan Bantuan Barang Di Usaha Kecil Menengah Pada Disperindagkop Provinsi Kalimantan Timur - Achmad Ariesta Obos; Andi Haerul Fauzan Ramadhan; Anggi Saputra; Muhammad Hafizh Mas’Ud; Sultan Ali; Muhammad Taufiq Sumadi (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
This research aims to develop an application for receiving goods assistance for small and medium enterprises (SMEs) in East Kalimantan Province. This application is designed to help the Department of Industry, Trade, Cooperatives, and SMEs of East Kalimantan Province to facilitate the input and output of data on SME submission goods that have been registered with the cooperative. The method used in this research is the Prototype Method. The Prototype method is an early version of a software system stage that is used to present an overview of ideas, experiment a design, find as many problems as possible and find solutions to problem solving. This method aims to describe the functions, features, and interfaces of the product more concretely. The results show that this application will allow assistance applicants to apply online, track the status of their application, and receive notifications about the progress of the application. In addition, this application will also make it easier for officers to manage and process applications, thereby minimizing errors and increasing efficiency. In conclusion, with this application, it is expected that the process of receiving goods assistance for SMEs can become faster, easier, and more transparent, which will ultimately support the development of SMEs in East Kalimantan Province.